DEVELOPMENT OF STUDENT WORK SHEETS GUIDED INQUIRY MODEL ORIENTED BY CRITICAL THINKING ACTIVITIES IN VIBRATION, WAVE, AND SOUND MATERIALS IN CLASS VIII SMPN 31 PADANG - Annisa Sri Hartina; Amali Putra (Universe, 2021)
Science teachers in developing learning models not only aim to improve cognitive, affective and psychomotorik aspects, but also aspects of studenst critical thinking skills. Low learning outcomes and lack of interest in learning are the result of a lack of critical thinking skills. Teaching materials used by school are not oriented towards critical thinking activities so students are not trained in critical thinking. One solution to these problems is that in learning the teacher must use the right learning model and the right teaching material. The study aims to develop student work sheets guided inquiry model which is oriented towards critical thinking activities for grade VIII SMP/MTs and reveal the level of validity from the veloped Student work sheets. The type of research used is Research and Development model (R&D) using the Plomp development model. The Plomp development model consisting of three stages, they are preliminary research, prototyping phase, and assessment stage. In this study only research the prototyping phase with expert riview. The research instrument used was a questionnaire in the form of a validity sheet validated by four validators. Based on the results of the study found a validation value of 90% with a very valid category.